Liraglutide mitigates TNF‐α induced pro‐atherogenic changes and microvesicle release in HUVEC from diabetic women. Issue 8 (6th September 2017) - Di Tomo, Pamela; Lanuti, Paola; Di Pietro, Natalia; Baldassarre, Maria Pompea Antonia; Marchisio, Marco; Pandolfi, Assunta; Consoli, Agostino; Formoso, Gloria
Abstract: Background: To evaluate whether exposure to GLP‐1 receptor agonist Liraglutide could modulate pro‐atherogenic alterations previously observed in endothelial cells obtained by women affected by gestational diabetes (GD), thus exposed in vivo to hyperglycemia, oxidative stress, and inflammation and to evaluate endothelial microvesicle (EMV) release, a new reliable biomarker of vascular stress/damage. Methods: We studied Liraglutide effects and its plausible molecular mechanisms on monocyte cell adhesion and adhesion molecule expression and membrane exposure in control (C‐) human umbilical vein endothelial cells (HUVEC) as well as in HUVEC of women affected by GD exposed in vitro to TNF‐α. In the same model, we also investigated Liraglutide effects on EMV release. Results: In response to TNF‐α, endothelial monocyte adhesion and VCAM‐1 and ICAM‐1 expression and exposure on plasma membrane was greater in GD‐HUVEC than C‐HUVEC. This was the case also for EMV release. In GD‐HUVEC, Liraglutide exposure significantly reduced TNF‐α induced endothelial monocyte adhesion as well as VCAM‐1 and ICAM‐1 expression and exposure on plasma membrane. In the same cells, Liraglutide exposure also reduced MAPK/NF‐kB activation, peroxynitrite levels, and EMV release. Conclusions: TNF‐α induced pro‐atherogenic alterations are amplified in endothelial cells chronically exposed to hyperglycemia in vivo. Liraglutide mitigates TNF‐α effects and reduces cell stress/damage indicators, such as endothelial microvesicle (EMV) release. These results foster the notion that Liraglutide could exert a protective effect against hyperglycemia and inflammation triggered endothelial dysfunction.